Afijación óptima de tamaños de muestra en muestreo aleatorio estratificado vía programación matemática (2010)
Somesamplingallocationproblemswhichcanbesolvedbymathematicalprogramming techniques are considered. Optimal allocation of sample sizes in Stratiﬁed Random Sampling (SI.), for example, can be regarded as a dynamic programming problem. In the multivariate case, the underlying convex–programming problem is stated and some solution methods are indicated. We have followed the illuminating ideas exposed in Arthanari & Dodge (1981). Finally, an example to illustrate the so-called Knapsack method is presented.